2011
DOI: 10.3168/jds.2010-3626
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that leptin genotype is associated with fertility, growth, and milk production in Holstein cows

Abstract: This study investigated associations between single nucleotide polymorphisms (SNP) in the leptin, leptin receptor, and neuropeptide Y (NPY) genes with growth, milk production, and fertility traits. Holstein Friesian heifers from 19 UK dairy farms were recruited at birth, providing an initial population of 509. Animals were monitored until they either reached the end of their second lactation or were culled. Size (weight, height, length, girth) was measured at 1, 6, and 15 mo to assess growth traits. Heifer fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 54 publications
8
83
0
3
Order By: Relevance
“…In our study leptin SNPs were more strongly associated with fertility than with milk production (Clempson et al 2011b). Of five different leptin SNPs investigated, all were significantly associated with some aspect of fertility, including age at first service and services per conception in heifers, age at first calving, days to conception, proportion in-calf at 100 days post partum and calving interval.…”
Section: Leptinmentioning
confidence: 80%
See 1 more Smart Citation
“…In our study leptin SNPs were more strongly associated with fertility than with milk production (Clempson et al 2011b). Of five different leptin SNPs investigated, all were significantly associated with some aspect of fertility, including age at first service and services per conception in heifers, age at first calving, days to conception, proportion in-calf at 100 days post partum and calving interval.…”
Section: Leptinmentioning
confidence: 80%
“…In contrast, only one SNP in our study (A59V) was associated with milk yield, although other studies have found some associations of leptin SNPs with milk yield and composition (van der Lende et al 2005;Banos et al 2008). An SNP in neuropeptide (NPY) was also significantly associated with the in-calf rate at 100 days (Clempson et al 2011b). NPY is a neurotransmitter that controls appetite and energy homeostasis and is a key regulator of leptin activity in the hypothalamus (Bahar and Sweeney 2008).…”
Section: Leptinmentioning
confidence: 99%
“…DeVuyst et al (2008) reported an association between a leptin SNP and weaning weight in crossbred calves, while polymorphisms in the leptin receptor were associated with growth traits in Nanyang cattle, where they had significant effects on height, length, heart girth, weight and ADG at 6 and 12 months of age (Guo et al, 2008). Mixed model analyses revealed that leptin SNP in Holstein-Friesian heifers were similarly associated with early skeletal growth and also with fertility and subsequent milk production (Clempson et al, 2011). The association of leptin SNP with fertility traits in heifers suggested that the actions on fertility were direct and not mediated via altered tissue mobilisation as might occur during lactation.…”
Section: Genetic Selectionmentioning
confidence: 99%
“…LEP, the fat derived protein hormone, has a variety of physiological functions such as regulation of feed intake, energy balance, and fertility and immune functions (Tanpure et al, 2012). Genetic polymorphisms within the bovine LEP gene were found to be associated with growth, fertility and milk production in Holstein cows (Clempson et al, 2011;Tanpure et al, 2012).…”
Section: Introductionmentioning
confidence: 99%